Key Knowledge Gaps to Fill at the Cell-To-Ecosystem Level in Marine B-Vitamin Cycling - Wienhausen, Gerrit; Bittner, Meriel J.; Paerl, Ryan W. (Frontiers in Marine Science, 2022)
B-vitamins are essential micronutrients for marine plankton. Additionally, we now know many marine plankton cannot synthesize B-vitamins de novo (from scratch) and thus are reliant on external supplies. Details of B-vitamin exchange, whether ‘active’ or ‘passive’ (i.e. through cell secretion or mortality), are lacking and as a result we struggle to predict microbial physiology, community composition and biogeochemistry. We argue that significant advances in understanding of the impact of B-vitamin exchange and cycling on marine community structure and biogeochemistry can be made by focusing on unknowns related to the ‘in’s and out’s’ of B-vitamin transport, exchange between plankton, and ecosystem scale processing/transformation of B-vitamins. We point out that it is particularly necessary to reach beyond traditional categorization of populations as B-vitamin auxotrophs (requiring supplied vitamin) or prototrophs (de novo vitamin synthesizers) and begin addressing which populations are net ‘providers’ and/or ‘consumers’. This is a particularly interesting problem as organisms cannot be confidently categorized as net ‘providers’ and/or ‘consumers’ based on genome-based prediction, and it is possible the two roles may change over time and environmental conditions. We posit that greater knowledge of B-vitamin exchange, e.g. cross-feeding, acquisition and secretion systems, environmental triggers of ‘provision’ and ‘consumption’, will reveal unforeseen networking and novel niches across marine planktonic communities. Last, we advocate for further experiments tracking the responses of isolates or natural communities relative to vitamin availability, tracing flow of B-vitamins between cells using novel approaches (e.g. isotopic, fluorometric), and greater consideration of altered B-vitamin exchange and cycling under future climate scenarios.